Boosting English Vocabulary Proficiency in EFL Learners: A Study on the Efficacy of Quizizz at IAIN Kediri - Nugraheni, Revina; Fakhurriana, Ria (Indonesian Journal of Multidisciplinary Educational Research, 2023)
Vocabulary is one of the three elements of language, the building material, and the basics of language. The study aims to determine whether the interactive and gamified nature of Quizizz positively impacts the vocabulary acquisition process for EFL students. Quizizz is a game-based educational app, which brings multiplayer activities to classrooms and makes in-class exercises interactive and fun. This research study investigates the effectiveness of utilizing the Quizizz game application as a tool to enhance English vocabulary among students learning English as a foreign language (EFL). The research design of this study was quantitative design. The subject of the study were 30 students of EFL IAIN Kediri. The data was collected by asking the students to fill the questionnare. The data analysis was implementing the Likert Scale. The result of the study showed positive effect. It is hoped that this paper can improve english vocabulary and make vocabulary learning easy.